2011
DOI: 10.1253/circj.cj-11-0045
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Fibrinogen A.ALPHA. Chain Fragment Increases in Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background:The cause of chronic thromboembolic pulmonary hypertension is unknown and there is no specific circulating biomarker for its detection. The aim of the present study was to use proteomic analysis to detect serum biomarkers by evaluating the serum profiles of low-molecular-weight peptides using matrix-assisted laser desorption/ ionization time-of-flight/time-of-flight mass spectrometry in patients with chronic thromboembolic pulmonary hypertension. Methods and Results:Serum low-molecular-weight peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Subsequently, several studies confirmed that increased plasma/serum levels of fibrinogen are detectable in CTEPH (and PH) patients as compared to unaffected controls [25,26], supporting the idea that fibrinogen from patients carrying the Aα Thr312Ala polymorphism (or other polymorphisms affecting the structure of fibrinogen) is indeed more resistant to lysis. Finally, in 2013, Li et al confirmed in a large study including 101 CTEPH, 102 PE (without PH), and 108 healthy controls a higher genotype and allele frequency for the Aα Thr312Ala polymorphism in CTEPH [27].…”
Section: Polymorphismsmentioning
confidence: 89%
“…Subsequently, several studies confirmed that increased plasma/serum levels of fibrinogen are detectable in CTEPH (and PH) patients as compared to unaffected controls [25,26], supporting the idea that fibrinogen from patients carrying the Aα Thr312Ala polymorphism (or other polymorphisms affecting the structure of fibrinogen) is indeed more resistant to lysis. Finally, in 2013, Li et al confirmed in a large study including 101 CTEPH, 102 PE (without PH), and 108 healthy controls a higher genotype and allele frequency for the Aα Thr312Ala polymorphism in CTEPH [27].…”
Section: Polymorphismsmentioning
confidence: 89%
“…This study is notable for its incorporation of plasma protein depletion techniques, specifically albumin and immunoglobulin G. Despite immunodepletion of these two highly abundant proteins, penetration into the lower abundant proteome proved difficult. To overcome this dynamic range problem, Nomura and colleagues took advantage of a high‐throughput workflow that utilizes MALDI TOF/TOF MS of low molecular weight serum peptides from CTEPH patients. This technique employs magnetic beads with various surface chemistries in lieu of SELDI technology, and identified fibrinogen A alpha chain fragment as increased in CTEPH.…”
Section: Proteomics Has Already Catapulted Research In Phmentioning
confidence: 99%
“…12 In proteomic analysis, serum levels of the fibrinogen Aα chain fragment were found to be higher in chronic thromboembolic pulmonary hypertension. 13 Therefore, the spectrum of CVD in which fibrinogen is emerging as either a marker of increased risk or a contributor to the pathogenesis is expanding. It has been proposed that the fibrinogen level may be included in the risk stratification of CVD.…”
Section: Fibrinogen: a Marker Of Risk For Cvdmentioning
confidence: 99%